INFLUENCE OF UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA ON THE COURSE OF THE DISEASES OF BILIARY TRACT OF YOUNG AGE PERSONS - Reznichenko, O.G.; Pylypenko, N.O.; Gridnieva, S.V. (World of Medicine and Biology, 2019)
Connective tissue, which makes 50-80% of the body weight, plays a special role in the human body. Due to the main component of the connective tissue - elastin - the vascular walls, the heart and the lungs tissues, the intestinal wall have elastic properties. Undifferentiated CTD (UCTD) is diagnosed if a set of phenotypic symptoms in a patient does not match any of the differentiated diseases. The frequency of UCTD detection among young people reaches 80%. The high prevalence of the UCTD syndrome (66.9%) is determined in patients with functional diseases of the biliary tract, affecting the clinical manifestations of these diseases. Patients with severe UCTD display the highest frequency of the biliary tract motor disorders, as well as asthenic syndrome and vegetative dysfunction. In addition, with the UCTD syndrome in patients with functional disorders of the cardiovascular system, functional disorders of the biliary tract are observed in 43% of cases. Thus, the high prevalence of the UCTD syndrome indicates the need for early detection of the connective tissue dysplasia signs in young people in order to timely perform a set of preventive and therapeutic measures.